2023
DOI: 10.1049/qtc2.12070
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Key Distribution for V2I communications with software‐defined networking

Alexandros Stavdas,
Evangelos Kosmatos,
Carsten Maple
et al.

Abstract: The evolution of Connected and Autonomous Vehicles (CAVs) promises improvements in our travel experience and the potential to enhance road safety and reduce environmental impact. This will be utilising highly diverse traffic environments that enable several advanced mobility applications. A secure, efficient, reliable, and resilient communications infrastructure is required to support developments in these CAV systems. Next generation of telecommunication networks will seamlessly integrate terrestrial, satelli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Given the growing significance of cooperative driving technologies and their vulnerability to cyber threats, security is crucial. Incorporating Quantum Key Distribution into vehicle-to-infrastructure networks safeguards against quantum computational advances, ensuring secure data communication in urban settings [44]. A similar concern is tackled by [45], focusing on a novel framework for robust autonomous navigation in challenging, unfamiliar environments with mobility-stressing factors like uneven terrain, steep slopes, negative obstacles, and limited visibility due to dust or fog.…”
Section: Connected Infrastructure and Intelligent Transportation Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the growing significance of cooperative driving technologies and their vulnerability to cyber threats, security is crucial. Incorporating Quantum Key Distribution into vehicle-to-infrastructure networks safeguards against quantum computational advances, ensuring secure data communication in urban settings [44]. A similar concern is tackled by [45], focusing on a novel framework for robust autonomous navigation in challenging, unfamiliar environments with mobility-stressing factors like uneven terrain, steep slopes, negative obstacles, and limited visibility due to dust or fog.…”
Section: Connected Infrastructure and Intelligent Transportation Systemsmentioning
confidence: 99%
“…The system addressed the absence of GPS, degraded perception, and the lack of prior maps, necessitating real-time on-board computation using noisy sensor data. In this context, Stavdas et al [44] suggested integrating a cryptographic protocol into vehicle-to-infrastructure networks to protect against advancements in quantum computing, thereby ensuring secure data communication in urban settings. However, connected autonomous vehicles represent a significant opportunity for shaping efficient transportation systems.…”
Section: Connected Infrastructure and Intelligent Transportation Systemsmentioning
confidence: 99%